PENGARUH BERKUMUR LARUTAN TEH HITAM (BLESS TEA) DALAM MENURUNKAN AKUMULASI PLAK PADA GIGI ANAK USIA SEKOLAH DASAR - Rahminingrum Pujirahayu (HUMAN CARE JOURNAL, 2020)
The number of dental and oral problems in Indonesia is still quite high, especially dental caries. The purpose of this study was to determine the effect of rinsing using black tea solution (Bless tea) in reducing plaque accumulation in dental elementary school children. This type of research is quasi-experimental with pre-test and post-test group design. Respondents were selected based on the total sampling method in the students of SD Negeri 51 Poasia Kendari, aged 7-8 years and obtained as many as 40 respondents. The research variables are black tea solution (bless tea) and dental plaque. The average before rinsing using black tea solution (bless tea) was 3.10 ± 1.3 and the average after rinsing using black tea solution (bless tea) was 1.81 ± 0.7. There was a decrease with the difference before and after 1.09 ± 0.6. The analysis showed that there was a significant difference between plaque accumulation data before and plaque accumulation data after rinsing the black tea solution (bless tea) (p = 0,000). The results of the analysis showed a significant difference between the reduction in dental plaque accumulation in the intervention group and the control group (p = 0.03). The reduction in plaque accumulation in the intervention group rinsed with a black tea solution (blessing tea) was smaller than the control group rinsed with 0.2% chlorhexidine. The conclusion of the study is that there is an effect of rinsing the black tea solution (Reducing Tea) in Reducing the Accumulation of Dental Plaque in Primary School Children aged 7-8 years.